First record of Stempfferia insulana (Aurivillius, 1923) from Gabon, Central-West Africa - Tom Jamonneau (Contributions to Entomology)
This note is grounded in the examination of Afrotropical butterflies belonging to the entomological collections at CBGP, Montpellier, France. In the course of historical specimen referencing, the species Stempfferia insulana (Aurivillius, 1923; Lycaenidae) was recorded from Gabon. This is the first report of this species for this country, and the most western data for this Central-Western African species.